IMPLEMENTASI PROGRAM SERTIFIKASI PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KELURAHAN GUNUNG JATI KOTA KENDARI - Chika Zafa Librasti; Muhammad Basri; Aminuddin Aminuddin (Universitas Halu Oleo, 2020)
The problem of this research is how the implementation of the certification program PTSL in the village of Gunung Jati, Kendari and factors affecting the implementation of the certification program PTSL in the village of Gunung Jati, Kendari. The purpose of this study is to investigate the implementation of a certification program PTSL in the village of Gunung Jati, Kendari and factors affecting the implementation of the certification program PTSL in the village of Gunung Jati, Kendari. The method used in this research is descriptive qualitative. Data obtained using literature studies, field studies, and interviews. The results showed that the implementation of the certification program PTSL in the village of Gunung Jati, Kendari through the stages of counseling, data collection, measurement, adjukasi committee hearings, announcement and endorsement, as well as the issuance of the certificate has been running well and are in accordance with the terms and conditions determined. However, in the implementation of PTSL there are factors that affect the implementation, namely: communication factors, human resources, and the structure of the bureaucracy as the factors that most influence. Meanwhile, the disposition factors or characteristics of the factors most implementor as little influence.